2023
DOI: 10.1159/000528319
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for Reality: A Randomized Trial on Immersive Virtual Reality for Bronchoscopy Training

Abstract: <b><i>Background:</i></b> Bronchoscopy is an essential procedure in the diagnosis and treatment of pulmonary diseases. However, the literature suggests that distractions affect the quality of bronchoscopy and affect inexperienced doctors more than experienced. <b><i>Objectives:</i></b> The objective of the study was as follows: does simulation-based bronchoscopy training with immersive virtual reality (iVR) improve the doctors’ ability to handle distractions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…In addition to knowledge improvement, the VR group also showed higher confidence levels in managing patients with PROM, performing CS as an operator, and understanding the indications and complications of CS. This finding is consistent with previous studies that have demonstrated the positive impact of VR simulation on learners’ confidence and self-efficacy in various medical specialties 14 16 . The ability to practice and repeat specific tasks in a realistic virtual environment can boost learners’ confidence in their skills and decision-making abilities, especially in these critical areas of obstetric care.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to knowledge improvement, the VR group also showed higher confidence levels in managing patients with PROM, performing CS as an operator, and understanding the indications and complications of CS. This finding is consistent with previous studies that have demonstrated the positive impact of VR simulation on learners’ confidence and self-efficacy in various medical specialties 14 16 . The ability to practice and repeat specific tasks in a realistic virtual environment can boost learners’ confidence in their skills and decision-making abilities, especially in these critical areas of obstetric care.…”
Section: Discussionsupporting
confidence: 93%
“…For teaching and training, IVR was first used for emergency and resuscitation training scenarios [39] and is now also used for airway assessment. A recent study in bronchoscopy shows that IVR simulation training improves the quality of diagnostic bronchoscopy in a simulated scenario with distractions compared to conventional simulation-based training [40].…”
Section: Immersive Virtual Reality Simulatorsmentioning
confidence: 99%